Pengaruh Mobilisasi Dini terhadap Berkemih Spontan Pasca Bedah Sesar dengan Anestesi Spinal di Rumah Sakit TK. IV IM 07.01 Lhokseumawe - Afifah Nur; Anna Millizia; Teuku Yudhi Iqbal (Publikasi Indonesia, 2022)
Cesarean section requires anesthetic efforts to relieve pain in the patient. The type of anesthesia commonly used is spinal anesthesia. Urinary retention is one of the side effect on using spinal anesthetic drugs caused by blockade of spinal cord conduction as high as the S2-S4 segment which innervates the urinary bladder which can lead to UTI. One of the actions that can accelerate spontaneous voiding is early mobilization step by step after cesarean section. This study aims to determine the effect of early mobilization on spontaneous voiding after cesarean section with spinal anesthesia at Level IV IM 07.01 Hospital Lhokseumawe. Method that used in this research is quasi-experimental design with one-group posttest-only design, a population of 53 mothers after cesarean section with spinal anesthesia at Level IV IM 07.01 Hospital Lhokseumawe in October - November 2021. Data analysis used univariate and bivariate with Fisher Exact Test with 95% confidence level, = 5%. The result showed there was an effect of early mobilization on spontaneous voiding after cesarean section with spinal anesthesia at Level IV IM 07.01 Hospital Lhokseumawe with p value = 0.037 and OR = 6.346 (95% CI = 1.091-36.921). The conclusion of the study that there is an effect of early mobilization on spontaneous voiding after cesarean section with spinal anesthesia at Level IV IM 07.01 Hospital Lhokseumawe in 2021 and early mobilization had an effect 6 times on the initial time of voiding.